Pengujian Temporal Motivation Theory Sebagai Perantara Hubungan Optimisme dan Flow Akademik - Cyntia Maria Poedjianto Adi; Listyo Yuwanto; Kristianto Batuadji (Jurnal Ilmiah Psikologi MIND SET, 2014)
Based on research of Beard (2008) and Ali (2013), optimism is related with flow. Academic flow can be explained by framework of Temporal Motivation Theory (TMT) which consists of expectancy, low value, and impulsiveness (Yuwanto, 2013). Based on literature studies, there is lack of research about relation between optimism and flow based on TMT framework. In this study, researcher tested TMT as a moderate variable of relationship between optimism and academic flow. Respondents in this research are 146 students class of 2013, Faculty of Psychology Universitas Surabaya. This research use Life Orientation Test-Revised (LOT-R) for measuring optimism, The Flow Inventory for Students (LIS) for measuring academic flow and Steel Procrastination Scale (SPS) for measuring TMT. The result reveals that optimism has positive relation with academic flow (r=0.187, p=0.012). Measurement of TMT as moderate variable is done by partial correlation, by controlling expectancy, low value and impulsiveness. The result show no correlation (r= -0.096, p=0.127). This study concludes that expectancy, low value, and impulsiveness are variable which can explain more about relationship between optimism and academic flow. Optimism is not enough to reach academic flow, high expectancy, low value and low impulsiveness are needed to reach high academic flow.